ANALISIS PENDIDIKAN KARAKTER DALAM NOVEL BIOGRAFI MERRY RIANA “MIMPI SEJUTA DOLAR” KARYA ABERTHIENE ENDAH - Wirda Linda (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2020)
This study uses a qualitative descriptive method. This study aims to describe the character education in Merry Riana's biographical novel. The data collection technique is carried out using content analysis techniques. The data source of this research is the biographical novel of Merry Riana by Alberthiene Endah. The data analysis technique uses a descriptive method. by describing the facts and analyzing them. The results of this study prove that character education in the novel Biography of Merry Riana by Alberthiene Endah is (1) Religious, (2) Responsibility, discipline, independence, (3) Amanah, (4) Respect and courtesy, (5) Caring and cooperation. , (6) Creative and never give up.